A method of solving inverse problem of electro-logging - N. L. Mirontsov (Геофизический журнал, 2012)
A method of solving inverse problem of logging sounding has been proposed based on the possibility to take into account quantitative connection between a measurement inaccuracy and inversion inaccuracy. A possibility has been analyzed of taking into account an inaccuracy of existing methods of solving inverse problems of electrologging effectively. Efficiency of applying the table connecting the layer model parameters with the data of measurements in course of interpretation has been estimated. Examples of comparing results obtained by the method proposed and the other one used now on the real borehole material have been given It has been shown that a method proposed makes possible to distinguish the layers with penetration and without applying additional information on collector properties of their section.